Synthesis, Characterization and Luminescence Behavior of a Cd‐terephthalate Coordination Polymer. Issue 12 (26th March 2021) - Liu, Fujie; Jia, Qiangqiang; Wang, Guoxi
Abstract: A novel coordination polymer [CdBr(TA)](C2 H7 N)n was synthesized based on CdBr2 and terephthalic acid (TA) via solvothermal method, which belongs to orthorhombic system with Fddd space group, and it displays three‐dimension and 3‐fold interspersed. The compound was characterized by powder X‐ray diffraction, elemental analysis, thermal stability, fluorescence and ultraviolet absorption characterization to prove the phase purity and properties. Fluorescence test was proved that the compound has a strong fluorescence emission at 460 nm. When detecting metal ions, Cu 2+ and Fe 3+ ions have a complete quenching effect on their fluorescence, and Co 2+ ions could change its fluorescence emission wavelength. Abstract : A novel Cd complex was synthesized, which possesses strong fluorescence emission, and Cu 2+ and Fe 3+ have quenching effect on the fluorescence. Interestingly, Co 2+ makes the fluorescence blue shift. Furthermore, the reason of blue shift is studied by UV.